2015
DOI: 10.1089/end.2014.0763
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Omitting Cortical Renorrhaphy During Robot-Assisted Partial Nephrectomy: A Matched Analysis

Abstract: Omission of cortical renorrhaphy appears feasible with no urine leaks or bleeding complications observed. The percent renal volume loss was improved by omission of cortical renorrhaphy. Reconstruction technique is important to control for when studying renal function after partial nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 18 publications
2
48
0
5
Order By: Relevance
“…The sutures further damage the renal parenchyma causing devascularized volume loss. In line with our findings, Bahler et al [29] who evaluated functional volume loss after tumor enucleation reported an advantage of the non-renorrhaphy technique over standard sutures. Patients who were managed with running sutures of the base of tumor bed only had almost twofold increases in the preserved viable renal tissue [29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The sutures further damage the renal parenchyma causing devascularized volume loss. In line with our findings, Bahler et al [29] who evaluated functional volume loss after tumor enucleation reported an advantage of the non-renorrhaphy technique over standard sutures. Patients who were managed with running sutures of the base of tumor bed only had almost twofold increases in the preserved viable renal tissue [29].…”
Section: Discussionsupporting
confidence: 92%
“…In line with our findings, Bahler et al [29] who evaluated functional volume loss after tumor enucleation reported an advantage of the non-renorrhaphy technique over standard sutures. Patients who were managed with running sutures of the base of tumor bed only had almost twofold increases in the preserved viable renal tissue [29]. They concluded that careful reconstruction of the tumor bed can reduce the amount of devascularized parenchyma, and is considered one of the most important modifiable factors for renal function preservation after NSS.…”
Section: Discussionsupporting
confidence: 92%
“…40 Some studies showed that omission of cortical renorrhaphy appears feasible with no urine leaks or bleeding complications observed. 41 They also reported that the percentage of renal volume loss was improved by omission of cortical renorrhaphy. Reconstruction techniques are important to control for postoperative hemorrhage and studying renal function after NSS.…”
Section: Sliding-clip Renorrhaphy and Barbed Suturementioning
confidence: 98%
“…Some studies showed that omission of cortical renorrhaphy appears feasible with no urine leaks or bleeding complications observed . They also reported that the percentage of renal volume loss was improved by omission of cortical renorrhaphy.…”
Section: Technical Advancementsmentioning
confidence: 99%
“…Efforts continue to understand post-PN renal function and to improve it with the aim to maximize the additional benefits the robot-assisted approach could bring. [9][10][11] In the present study, we aimed to identify whether differences in surgical details had an impact on post-RAPN renal function.…”
Section: Introductionmentioning
confidence: 99%